Politics and Economy of Banjarmasin Sultanate in the Period of Expansion of the Netherlands East Indies Government in Indonesia, 1826-1860 - Ahyat, Ita Syamtasiyah (TAWARIKH, 2012)
ABSTRACT: In the political aspect of the Sultanate of Banjarmasin, the government of the Netherlands East Indies managed to power the Sultanate of Banjarmasin with agreements made between the Government and the Sultan. These agreements were causing severe loss to the Sultanate which had an impact on the nobility and the ordinary people. The Dutch government also managed to make the Sultanate of Banjarmasin powerless and made the Sultanate into her territory, so the Sultanate of Banjarmasin was no longer sovereign. The Dutch government put her representatives in Banjarmasin and managed to rule the economic potential was owned by the Sultanate which is the coal mines. Banjarmasin Sultanate eventually collapsed into the territory of the Netherlands East Indies government in 1860, resulting in a change of government in Banjarmasin. Sultan no longer existed, that there arose Banjarmasin war against the government of the Netherlands East Indies. Furthermore, the Sultan families, the nobility, and common people were hand in hand to rebel against the Netherlands government, which was well known as âBanjarmasin Warâ.KEY WORDS: Sultanate of Banjarmasin, Netherlands East Indies government, conflict in politics and economy, and Banjarmasin war.Â About the Author: Dr. Ita Syamtasiyah Ahyat is a Senior Lecturer at the Study Program of History, Department of History, Faculty of Humanities UI (University of Indonesia), UI Campus, Depok, West Java, Indonesia. She can be reached at: ita_ahyat@yahoo.co.idHow to cite this article? Ahyat, Ita Syamtasiyah. (2012). âPolitics and Economy of Banjarmasin Sultanate in the Period of Expansion of the Netherlands East Indies Government in Indonesia, 1826-1860â in TAWARIKH: International Journal for Historical Studies, Vol.3(2) April, pp.155-176. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 11, 2012); Revised (March 23, 2012); and Published (April 28, 2012).